Introduction to performance incentives: ten reasons why incentives don’t work - Jones, Stephanie (Henry Stewart Talks, 2020)
What incentives can do for your business, Managing an incentive strategy, 10 problems with sales incentives, Signs that your incentive plan is working, How to implement your incentive plans